Application of a Mytilus edulis-derived promoting calcium absorption peptide in calcium phosphate cements for bone. (March 2022) - Xu, Zhe; Zhu, Zhixuan; Chen, Hui; Han, Lingyu; Shi, Pujie; Dong, Xiufang; Wu, Di; Du, Ming; Li, Tingting
Abstract: The IEELEEELEAER peptide (PIE) identified from the protein hydrolysate of Mytilus edulis is reported to enhance osteoblast growth and differentiation, which also possesses a superior bone formation ability both in vitro and in vivo . Moreover, PIE bound to calcium spontaneously at the stoichiometry of 1:1, and there were amino nitrogen and carboxyl oxygen atoms in 2 glutamic acid residues at the calcium-binding sites in the PIE. The PIE–calcium complex facilitated calcium uptake through the Caco-2 cell monolayers. Incorporation of PIE into calcium phosphate cements enhanced calcium ion uptake and proliferation of osteoblasts and inhibit bacteria. This study suggest that calcium phosphate cements supplemented with PIE can serve as a potentially efficient material for bone graft used during spinal surgery. Graphical abstract: Image 1